Shaping library’s social media authority through trust -creating activities: A case of selected academic libraries in Nigeria - Sani Magoi, Joshua; Abrizah, A.; Yanti Idaya Aspura, M.K. (Malaysian Journal of Library and Information Science, 2020)
Trust and authority are emerging as key elements of success on social media environment. In spite of a burgeoning field of social media research, the topic on how institutions earn users’ trust and establish their social media authority has received very little attention to date. This study describes how academic librarians strategize in creating trust in social media contents and orient their actions towards the goals of achieving social media authority as information experts. The study is guided by the following research question: What are the trust-creating activities that academic librarians do on library’s social media to establish social media authority? Data were collected through interviews with 15 librarians from three Nigerian university libraries. Six themes on trust-creating activities emerged from the findings. Three themes are related to trust-creating activities by individual librarians: (a) post credible and useful social media contents; (b) provide relevant and responsive feedback; and (c) have authorized identification or social media icons. Another two themes are associated with trust-creating activities by librarians as a group: (a) collaborate in assessing social contents; (b) be an authority in library and information services. One trust-creating activity taken by the library management emerged i.e. involving the university authority for content. The researchers offer suggestions for librarians to orient their actions towards the goals of achieving social media authority and the distinctions are made in the trust- creating activities between individual, group and organisation. This paper contributes to the under-researched field investigating the actual implementation of social media authority in libraries. The study has shown that social media authority is built on the platter of users’ trust. Based on this observation, we believe that successful implementation of social media in the library is associated with not only how proficient librarians are in social media use, but also how they build their social media contents through trust-creating activities.